Kratom use and mental health: A systematic review. (1st February 2018) - Swogger, Marc T.; Walsh, Zach
Highlights: Kratom ( Mitragyna speciosa ) is a psychoactive plant that is receiving increased international attention. Kratom use carries important mental health risks and benefits that require study. Kratom has harm reduction potential for substance users who want to quit opioids. Kratom enhances mood and relieves anxiety for some people. Kratom's withdrawal syndrome and dependence potential is (often) mild vs. opioids. Abstract: Background: Kratom ( Mitragyna speciosa ) is a psychoactive plant native to Southeastern Asia that is receiving increased international attention as a potential therapeutic agent. While much of the limited scientific research on kratom is focused on its analgesic potential, kratom use also has important risks and benefits in the domain of mental health. Methods: We conducted a comprehensive systematic review of all studies on kratom use and mental health published between January 1960 and July 2017. Results: Findings indicate kratom's potential as a harm reduction tool, most notably as a substitute for opioids among people who are addicted. Kratom also enhances mood and relieves anxiety among many users. For many, kratom's negative mental health effects – primarily withdrawal symptoms – appear to be mild relative to those of opioids. For some users, however, withdrawal is highly uncomfortable and maintaining abstinence becomes difficult. Conclusion: Results inform clinicians working in the mental health and substance use fields, policy-makers, and researchers about the mental health effects of this plant.